Pre, intra and postoperative evaluation in liver surgery.: SIMPOSIUM - Perrier, José Pedro (Cirugía del Uruguay, 2002)
Liver surgery presents tactical problems- technical and pre, intra and postoperative management that require a study and special dedication. Not for nothing was it one of the last to develop. The functional complexity of the liver and the repercussions metabolic that has its direct aggression; its structural fragility, determined by its fundamentally liquid content, a true blood and bile "sponge" and its anatomy biliary-veno-arterial crossroads challenged during centuries to the attempts of his surgical mastery